A Curious Case of Subacute Meningitis- Eosinophilic meningitis caused by Angiostrongylus cantonensis - Anandan, Somarajan; Rajendran, Sajeesh S.; Padmanabhan, Rihul (Nepal Journal of Neuroscience, 2001)
Presence of eosinophils in cerebrospinal fluid (CSF) is a very important clue for the aetiology of meningitis and has to be carefully looked by an experienced pathologist. Most of the time history reveals the origin of eosinophilic meningitis (EM). Angiostrongylus cantonensis is the most common cause of eosinophilic meningitis worldwide. Peripheral eosinophilia and CSF eosinophils can increase in spite of anthelmintics and treatment should include steroids in addition to anthelmintics. Here we describe a case of eosinophilic meningitis following consumption of meat of monitor lizard who presented with headache and diplopia without fever.